The Liquid Phase Catalytic Hydrogenation of the Furfural to Furfuryl Alcohol - Kseniya Salnikova; Valentina Matveeva; Alexey Bykov; Galina Demidenko; Irina Shkileva; Esther Sulman (Chemical Engineering Transactions, 2018)
The results of the study of palladium catalysts in the selective hydrogenation of furfural to furfural alcohol are presented. A comparison of the properties of palladium catalytic systems prepared on different supports (aluminium oxide, hypercrosslinked polystyrene and magnetite/hypercrosslinked polystyrene) is carried out. It is shown that the nature of the support has a significant impact on both the morphology of the catalyst and its activity in the selective hydrogenation of furfural. The most effective catalyst was magnetically recoverable 3 % Pd/Fe3O4/HPS, in the presence of which the conversion of furfural was> 95% with selectivity for furfuryl alcohol> 94 %.